Revisiting Student Stories: Understanding Microaggressions and Interpersonal Conflict Within Speech-Language and Hearing Sciences Training Programs. - Abdelaziz, Mariam M.; Rivera Pérez, Jean F. (American Journal of Speech-Language Pathology, 2024)
Purpose: The current study revisits our previous research, delving deeper into microaggressions (MAs) and interpersonal conflict (IC) in speech, language, and hearing sciences (SLHS) training programs. Participants came from both marginalized and nonmarginalized backgrounds. Method: A 39-item electronic survey based on our previous research was distributed online to 236 participants of current and former SLHS students through social media and e-mail listservs. Results: Students that identified as belonging to marginalized and nonmarginalized groups reported high levels of MAs and IC, respectively. Linear regression revealed that the more marginalized identities a participant reported, the more aggression they experienced. Analyses also suggest that specific cultural and linguistic identities more likely predicted experiencing specific types of MAs than others. MAs and IC were largely underreported. Conclusions: This study highlights the quantifiable prevalence of MAs and IC in SLHS training programs. It underscores the urgent need for targeted interventions to address systemic inequities. Overall, these findings emphasize the importance of fostering an inclusive and equitable environment in SLHS, promoting cultural competence, and social justice in the professions.